Keragaman Arthropoda pada Teknologi Bujangseta di Tanaman Jeruk Siam - Lisa Navitasari; Harwanto Harwanto; Joko Gagung Sunaryono; Eny Wahyuning Purwanti (Institut Pertanian Bogor, 2024)
Bujangseta is a technology used throughout the year to produce citrus fruits. This technology has economically succeeded in increasing the income of citrus farmers by 23.5%. Sustainable management of bujangseta technology is neede, one of which is maintaining the sustainability of the agroecosystem. A stable agroecosystem ensures the availability of ecosystem services through nutrient cycling and the natural control of pest and disease populations. The stability of agroecosystems is coherent with the high biodiversity of arthropods. This study aims to evaluate the effect of applying the citrus plant bujangseta in Karangwidoro village and Krajan village, Dau District, Malang Regency, East Java, from June to December 2022. The two application methods were light trapping (lighttrap) and pit trap (pitfall glass), and the results were analyzed using a t-test. The diversity index, species richness index, species evenness index, and dominance index were calculated. The results showed that the detrivores of the Collembola group dominated the diversity of arthropods, the primary pest of the Diaphorina citri, and the predatory arthropods of Paederus sp. and Braconidae. Diversity and community structure of arthopods indicated there at significant differences in diversity, dominance, evenness, and species richness in those two locations. Bujangseta in the Krajan has a higher community structure compared to the Karangwidoro, showing that the ecosystem at the Krajan location is better preserved. Keywords: arthropods, bujangseta, citrus, community structure